The Need for the Formation of Environmental Education and Upbringing in Young People in the Conditions of Environmental Globalization (Global Scientific Review, 2023)
The article expresses an opinion on the need for environmental knowledge, the introduction of innovative projects in ecology and the protection of environmental resources and the improvement of environmental culture. The formation of environmental education and its continuous improvement takes place on the basis of continuous education in secondary schools. Its predominantly traditional and innovative teaching enhances the effectiveness of education.